Acute stent malfunction in a calcified lesion. Issue 4 (2015) - Sinha, Santosh Kumar; Thakur, Ramesh; Jha, Mukesh Jitendra; Kumar, Asmutosh; Mishra, Vikash; Goel, Amit; Varma, Chandra Mohan; Krishna, Vinay
No abstract available